Photothermal hydrogels for infection control and tissue regeneration - Sun, Siyu; Jiang, Guangyang; Dong, Jianru; Xie, Xi; Liao, Jinfeng; Tian, Yongqiang (Frontiers in Bioengineering and Biotechnology, 2024)
In this review, we report investigating photothermal hydrogels, innovative biomedical materials designed for infection control and tissue regeneration. These hydrogels exhibit responsiveness to near-infrared (NIR) stimulation, altering their structure and properties, which is pivotal for medical applications. Photothermal hydrogels have emerged as a significant advancement in medical materials, harnessing photothermal agents (PTAs) to respond to NIR light. This responsiveness is crucial for controlling infections and promoting tissue healing. We discuss three construction methods for preparing photothermal hydrogels, emphasizing their design and synthesis, which incorporate PTAs to achieve the desired photothermal effects. The application of these hydrogels demonstrates enhanced infection control and tissue regeneration, supported by their unique photothermal properties. Although research progress in photothermal hydrogels is promising, challenges remain. We address these issues and explore future directions to enhance their therapeutic potential.